Optic Perineuritis Associated With Cryptococcal Meningitis Presenting With a "Hot Orbit" in a Patient With Chronic Lymphocytic Leukemia. Issue 2 (23rd June 2022) - Liebman, Daniel L.; Tam, Emily K.; Lithgow, Marie Y.; Kane, Joseph E.; Fischbein, Nancy J.; Lefebvre, Daniel R.; Chwalisz, Bart K.; Gaier, Eric D.
Abstract: A 75-year-old man presented with 3 days of progressive left retro-orbital pain, eyelid swelling, tearing, and pain with extraocular movement. His medical history was significant for type II diabetes mellitus and chronic lymphocytic leukemia, stable on no therapy since diagnosis 8 years prior. The initial examination was significant for diffuse restriction of left ocular motility, marked lid edema, and mild dyschromatopsia. Computed tomography demonstrated asymmetric left periorbital soft tissue swelling and intraconal fat stranding with an irregular left optic nerve sheath complex and clear paranasal sinuses. He was hospitalized for orbital cellulitis and treated empirically with broad-spectrum intravenous antibiotics, but his visual acuity declined over the ensuing 2 days. Subsequent MRI demonstrated left-greater-than-right circumferential optic nerve sheath enhancement, and leptomeningeal enhancement. An orbital biopsy demonstrated monoclonal B-cell lymphocyte aggregation, whereas a lumbar puncture was positive for Cryptococcus antigen with subsequent demonstration of abundant Cryptococcus by Papanicolaou stain. The final diagnosis was optic perineuritis secondary to cryptococcal meningitis presenting with orbital inflammation. Although his clinical course was complicated by immune reconstitution inflammatory syndrome, symptoms and signs of optic neuropathy ultimately resolved after 1 month of intensive antifungal therapy.